9.6k views
0 votes
Solve by elimination

Solve by elimination-example-1

2 Answers

4 votes

Answer:

X=9, y=-1

Step-by-step explanation:

Multiply 2nd equation by -3 so you can eliminate x

-3(-x-6y)=-3(-3)

3x+18y=9

add first equation to modified second equation:

-3x+y=-28

3x+18y=9

Solve. 19y=-19

Y=-1

Find x by substituting y value into either equation:

-3x+y=-28

-3x+-1=-28

-3x=-27

x-9

check answer by substituting x and y values into either equation.

-3x+y=-28

-3(9)+-1=-28

-27-1=-28

-28=-28

User Mario Uvera
by
6.0k points
5 votes

-3x+y = -28

-x-6y = -3

~~~~~~~~~~~~~

Eliminate x:

-3x+y=-28

-x-6y=-3

~~~~~~~~~~~~~

-3x+y=-28

-3(-1)x-3(-6)y=(-3)(-3)

~~~~~~~~~~~~~

3x-1y=28

3x+18y=9

19y=-19

Therefore:

19y=-19

÷19 ÷19

y=
(-19)/(19)

y=1

~~~~~~~~~~~~~

3x-1y=28

y=-1

~~~~~~~~~~~~~

3x-1(-1)=28

3x+1=28

-1 -1

3x=28-1

3x=27

÷3 ÷3

x=
(27)/(3)

↑ They cancel each other out

x=9

~~~~~~~~~~~~~

x=9

y=-1

Answer is: (9,-1)

User Qubz
by
5.4k points